Genetic variants associated with systemic inflammatory disease associate with temporomandibular symptoms with or without periodontitis - Courtney Lucas; Dylan Baxter; Kathleen Deeley; Nilesh Shah; Antonio Pugliano; Renato Silva; Ariadne Letra; Mariana Bezamat; Alejandro Almarza; Juan Taboas; Alexandre R. Vieira (PLoS ONE, 2026)
Introduction Associations of genetic polymorphisms reported to play a role in systemic inflammatory diseases may serve as proxies to assess predisposition for oral diseases, as well as identify biomarkers to support preventive measures and targeted therapies. Our goal was to assess if genetic variants previously associated with systemic inflammation are associated with temporomandibular symptoms (TMS). Methods We queried repository records to identify phenotypes (TMS and periodontitis) and systemic inflammatory diseases (asthma, obesity, rheumatoid arthritis/autoimmune disease, and type II diabetes mellitus; singular group based upon their shared inflammatory characteristic). Combinations of with and/or without systemic disease, TMS, and PD formed four groups. Single nucleotide variants (SNVs) in 15 genes ( ADAM10, AQP5, AXIN2, BRINP3, CA9, GSK3B, IL10, IL17A,IL1B, IL4, MMP2, MMP9, MYO1H, TGFB1, WNT11 ) were selected for TaqMan chemistry genotyping (genotypic/addictive and allelic association tests) to identify associations between each SNP and phenotypes of interest using gPLINK. Bonferroni correction was applied (α = 0.001) to denote statistical significance. Logistic regression analyses were conducted to identify associations between systemic and dental disease phenotypes. Results Associations were observed between SNPs in MMP9 with systemic disease phenotypes (asthma, obesity, rheumatoid arthritis/autoimmune disease, and type II diabetes mellitus) without oral disease phenotypes (TMS-, PD-) (p = 0.00004). The same systemic disease phenotypes with signs and symptoms of TMS (TMS + , PD-) were associated with SNPs in AXIN2 and MMP9 (p = 0.0001 and p = 0.000009, respectively) MMP9 was associated with the systemic disease phenotypes in the presence of periodontal disease, without TMS (TMS-, PD+) (p = 0.000008). An allelic association was found between the SNP in AXIN2 with the systemic disease phenotypes including TMS positive phenotypes (p = 0.0005). No assocations were found between all systemic and oral disease phenotypes after controlling for age and sex at birth. Conclusion This study showed that SNPs associated with systemic inflammation were also associated with oral diseases. These SNPs may be considered additional markers of oral disease.